1998
DOI: 10.1111/j.1439-037x.1998.tb00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Development and Stem Yield of Non‐domestic Fibre Hemp (Cannabis sativa L.) Cultivars in Long‐day Growth Conditions in Finland

Abstract: Plant development and stem yield of mono‐ and dioecious fibre hemp cultivars (Cannabis sativa L.), introduced to Finland from regions of lower latitude, were studied in field experiments under long‐day growth conditions in 1995–96. Plant density, plant mortality rate, stem elongation and stem yield were determined. Plant densities at seedling stage were less than the targeted viable seeds sown m−2. Seedling densities differed significantly among cultivars, but had no significant effect on plant mortality rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Stem length for Felina was 180 in the beginning of flowering and 204 cm at the end. In earlier studies (Sankari and Mela, 1998), the growth had been found to cease at flowering. However, usually hemp continues to elongate between the beginning and the end of flowering if climate circumstances are favorable for growth.…”
Section: Stem Elongation and Floweringmentioning
confidence: 96%
“…Stem length for Felina was 180 in the beginning of flowering and 204 cm at the end. In earlier studies (Sankari and Mela, 1998), the growth had been found to cease at flowering. However, usually hemp continues to elongate between the beginning and the end of flowering if climate circumstances are favorable for growth.…”
Section: Stem Elongation and Floweringmentioning
confidence: 96%
“…Hemp cultivation at high latitudes was considered to promote the high antioxidant capacity and nutritional quality of its seed and oil (Blade et al 2005). The industrial cultivar USO 11 was recommended for cultivation in Finland as an early-maturing variety (Sankari and Mela 1998). Other cultivars, such as USO 31, Beniko and Bialobrzeskie, were evaluated as suitable for the long-day growth conditions prevailing in Finland (Sankari 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation was carried out with the procedure commonly used in Finland (Sankari 1998, Hongisto et al 2000. Linseed was sown on both years (2001 and 2002) at a seed density of 68 kg ha -1 and hemp at ca.…”
Section: Cultivation Of the Plantsmentioning
confidence: 99%